THE EVOLUTION OF POLITICAL SCIENCE THROUGH THE LENS OF THE HISTORY AND PHILOSOPHY OF SCIENCE - Thary, Prom (Srawung: Journal of Social Sciences and Humanities, 2025)
The article examines political science development through historical and philosophical analysis to understand how the discipline has evolved its paradigms and methodological debates. The research starts by showing how political science evolved from its origins in Plato and Aristotle through the creation of contemporary Western and Eastern political systems. The research problem examines how different philosophical traditions and discourses have formed political science as a distinct field of study which leads to essential disagreements between researchers who focus on empirical transformations versus those who focus on ethical preservation. The research aims to establish a complete understanding of political science development through an analysis of its conceptual roots and historical impacts and philosophical interactions. The research uses critical qualitative analysis to study political science development through a combination of essential literature review and historical and comparative case study evaluation. The research shows that political science continues to exhibit methodological pluralism through its combination of empirical research with philosophical analysis. The article shows that constructivist and historical–causal frameworks serve as crucial tools for understanding political phenomena because they reveal their dynamic nature and their contested and context-dependent characteristics. The research demonstrates that contemporary governance challenges and ethical questions require interdisciplinary and reflexive approaches which support a political science that combines historical understanding with forward-looking analysis to remain relevant in the twenty-first century.